Requirements Model for Universiti Utara Malaysia Library Data Warehouse - Alwan, Haider Abdulkadhim (2012)
Requirements play a very important role in system development project. It is because requirement forms the backbone of any successful project and provide the measure of success or failure of a certain project. Misinterpretation of the requirements would increase cost and hinder the system development to meet user’s expectation. Therefore, it is necessary to present the requirement in an understandable and meaningful way. This is achieved through requirement model. The model gives a complete view of certain system and represents idea without having to develop an actual system. This research aimed to create a requirement model for Universiti Utara Malaysia Library Data Warehouse. Snowflake model is used to model the requirement. A set of requirement list is produced in this research. Various reports were produced and validated by the users. Several recommendations for future research were discussed.